A post-COVID syndrome curriculum for continuing medical education (CME): in-person versus livestream - Mueller, Michael; Ganesh, Ravindra; Schroeder, Darrell; Beckman, Thomas J. (Frontiers in Medicine, 2024)
Background: Nearly 30% of patients with COVID-19 infection develop post-COVID Syndrome. Knowledge of Post-COVID Syndrome is evolving, creating the need for adaptable curricula. Flipped classrooms (FC) are flexible and dynamic with demonstrated utility in continuing medical education (CME), yet there has been no research on application of FCs, or comparisons between livestream and in-person learning, in post-COVID CME.Methods: We implemented a novel post-COVID curriculum using FCs for in-person and livestream participants at four Mayo Clinic CME conferences. Outcomes were validated measures of knowledge; perceptions of FCs and CME teacher effectiveness; and learner engagement. Pre-conferences surveys were a post-COVID knowledge test and the Flipped Classroom Perception Inventory (FCPI). Post-conference surveys were a post-COVID knowledge test, the FCPI, the CME Teaching Effectiveness Instrument (CMETE), and the Learner Engagement Inventory (LEI). Pre-post knowledge and FCPI scores were analyzed using linear mixed models. CMETE and LEI were compared for in-person versus livestream participants using the Wilcoxon rank-sum test.Results: Overall, 59 participants completed the pre-test, and 72 participants completed the posttest, surveys. Participants were predominantly female (58%), were in nonacademic group practices (65%), and lacked prior experience with flipped classrooms (83%). Following the presentations, participants showed significant improvements in post-COVID knowledge (47% correct precourse to 54% correct postcourse, p-value = 0.004), and a trend toward improved FCPI scores. Teaching effectiveness, learner engagement, and pre-post change in COVID knowledge did not differ significantly between participants of in-person versus livestream sessions.Conclusions: This post-COVID FC curriculum was feasible and associated with improved knowledge scores among a diverse population of physician learners in CME, without any apparent compromise in learner engagement, or in perceptions of teaching effectiveness and FCs, among livestream versus in-person participants.